Efficacy of Bifidobacterium infantis 35624 in patients with irritable bowel syndrome: a meta-analysis. (3rd July 2017) - Yuan, Fuqiang; Ni, Huijuan; Asche, Carl V.; Kim, Minchul; Walayat, Saqib; Ren, Jinma
Abstract: Background: The treatment of irritable bowel syndrome (IBS) is a challenge because its cause remains unknown. Previous clinical trials to examine the efficacy of probiotic Bifidobacterium infantis 35624 ( B. infantis ) in patients with IBS have shown inconsistent findings. This study aimed to assess the combined effect of B. infantis on reducing the symptom severity of IBS based on the published data. Methods: A meta-analysis was conducted using fixed-effect models to estimate the combined effect of B. infantis on primary outcomes, which included abdominal pain, bloating/distention, and bowel habit satisfaction. A systematic review was performed based on PubMed, Cochrane Library, and EMBASE databases to identify the randomized controlled trials comparing probiotic B. infantis with placebo in treating IBS symptoms, published up until 31 December 2016. The standardized mean difference (SMD) method was used to combine data since scales to measure the efficacy of probiotics were different among studies. Results: A total of five studies were identified as suitable for inclusion, including three studies with single probiotic B. infantis and two studies with composite probiotics containing B. infantis . Treatment with single probiotic B. infantis didn't impact on abdominal pain, bloating/distention, or bowel habit satisfaction among IBS patients. However, patients who received composite probiotics containing B. infantis had significantly reduced abdominal pain (SMD, 0.22; 95% CI, 0.03–0.41) and bloating/distention (SMD, 0.30; 95% CI, 0.04–0.56). After combining the data from six studies, the improvement of bloating/distention among IBS patients remained significant (SMD, 0.21; 95% CI, 0.07–0.35). Conclusion: Composite probiotics containing B. infantis might be an effective therapeutic option for IBS patients, which could significantly alleviate the symptoms of IBS without significant adverse effects. However, the efficacy of single probiotic B. infantis on IBS has not been confirmed yet, which needs to be further validated by more large-sized randomized clinical trials.